COMPARISON OF MANUAL VACUUM ASPIRATION UNDER LOCAL ANESTHESIA AND SUBLINGUAL MISOPROSTOL IN MANAGEMENT OF INCOMPLETE MISCARRIAGE IN GMC TEACHING HOSPITAL, NEPAL - Tripathi, Malati; Sherchan, Kripa (Journal of Universal College of Medical Sciences, 2018)
Introduction: To compare the efficacy of using sublingual misoprostol and manual vacuum aspiration under local anesthesia in the treatment of spontaneous incomplete miscarriage (of up to 6 to 12 weeks of pregnancy). MATERIALS AND METHODS: This is a prospective study performed in Gandaki Medical College (GMC) Teaching Hospital, Pokhara on 150 patients with spontaneous incomplete miscarriage between 6 to 12 weeks of pregnancy. Patients were divided into two groups: group (I) patient who took 400 μg misoprostol every four hourly for maximum of three doses, group (II) patient who underwent manual vacuum aspiration (MVA) under local anesthesia. Only 68 patients in group I and 64 patients in group II completed their follow up and were included in this study. RESULTS: The success rate of MVA under local anesthesia was 100% and misoprostol was 67.7% (p-value <0.05). Both misoprostol and MVA under local anesthesia are effective for treatment of incomplete miscarriage. CONCLUSION: Although success rate of MVA under local anesthesia is more than misoprostol, both MVA and misoprostol can be used, as an effective method of uterine evacuation in incomplete abortion of <12 weeks. Journal of Universal College of Medical Sciences Vol. 6, No. 1, 2018, Page: 52-55